Silent bowel perforation with per anal protrusion of ventriculoperitoneal shunt - Sarvpreet Singh Grewal; Sukhdeep Singh Jhawar; Bharat Gupta; Nandini K Bedi (Wolters Kluwer Medknow Publications, 2014)
Ventriculoperitoneal (VP) shunt used in the treatment for hydrocephalus is associated with several complications. Visceral/bowel perforation is an unusual but serious complication of VP shunt. A silent protrusion of distal end of VP shunt per anus is reported in an 8-month-old male child. Patient underwent right VP shunt at the age of 6 months for congenital hydrocephalous. Patient was afebrile and had no signs of peritonitis or meningitis. Exploratory laparotomy was done where shunt was found to penetrate antimesenteric border of sigmoid colon. Shunt was removed and patient is doing well at 6 months follow-up without revision of VP shunt. Etiopathogenesis and management issues are discussed with relevant review of literature.